PENGARUH GENDER DIVERSITY EKSEKUTIF DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN TAX AVOIDANCE SEBAGAI INTERVENING - Andri Sjahputra; Sujarwo Sujarwo (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to obtain empirical evidence about the effect of executive gender diversity and firm size on firm value with tax avoidance as an intervening variable. This sampling technique uses non-probability sampling and this research was conducted using the Incidental Sampling method using the Slovin formula. Based on the test results, it was found that Executive Gender Diversity and Company Size (Size) had a simultaneous effect on Company Value with Tax Avoidance as an Intervening Variable. Tax avoidance cannot mediate gender diversity and firm size in influencing firm value. This confirms that the value of the company is not affected by the issue of tax avoidance, so that the relationship between the influence of ender diversity and company size tends to be direct.